1983
DOI: 10.1210/jcem-56-2-359
|View full text |Cite
|
Sign up to set email alerts
|

Human Seminal Plasma Contains a Protein that Shares Physicochemical, Immunochemical, and Immunosuppressive Properties with Pregnancy-Associated Plasma Protein-A*

Abstract: Pregnancy-associated plasma protein-A (PAPP-A) was detected by RIA in human seminal plasma. This was not due to interference with proteases or binding to seminal plasma proteins, since immunoreactivity was not affected by treatment with protease inhibitors, and the elution of [125I]PAPP-A was not altered by preincubation with seminal plasma. The major component of the seminal plasma PAPP-A coeluted with pure PAPP-A or plasma PAPP-A from pregnant and nonpregnant women. In the RIA, serial dilutions of seminal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…The observed correlation between PAPP-A and inhibition of lymphocyte transformation agrees with our previous data: removing PAPP-A-like material from seminal plasma reduced the inhibitory effect of seminal plasma on PHA-induced lymphocyte transformation [5]. It is interesting to note that for an unexplained reason, in vasectomized men, PAPP-A and lymphocyte transformation inhibition are no longer correlated.…”
Section: Discussionsupporting
confidence: 90%
“…The observed correlation between PAPP-A and inhibition of lymphocyte transformation agrees with our previous data: removing PAPP-A-like material from seminal plasma reduced the inhibitory effect of seminal plasma on PHA-induced lymphocyte transformation [5]. It is interesting to note that for an unexplained reason, in vasectomized men, PAPP-A and lymphocyte transformation inhibition are no longer correlated.…”
Section: Discussionsupporting
confidence: 90%
“…The performances of the different models were evaluated by Receiver Operating Characteristic (ROC) curve analysis with estimation of areas under the curve (AUROC). The quality-of-fit of models was assessed using r 2 and AIC (Akaike Information Criterion) [27]. Specificity, sensitivity, and predictive values were obtained for the logistic regression models.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Pregnancy Associated Plasma Protein (PAPP-A) is an important glycoprotein found in maternal blood that increases as pregnancy progresses [1], although it is not specific to pregnancy [2,3]. In pregnancy, PAPP-A is principally expressed in the syncytiotrophoblast of the placenta, which forms the main source of circulating maternal PAPP-A [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These include zinc, in both free and complex form [8], prostaglandin E (PGE) [7], uteroglobin and transglu taminase [9], spermine and spermidine [10], preg nancy-associated plasma protein A [11] and unchar acterized high molecular weight (HMW) substances [2,3,12]. It has been suggested that these factors pro tect sperm from immunological damage in the male, and prevent sensitization of the female to sperm anti gens after insemination.…”
Section: Introductionmentioning
confidence: 99%